UPAYA PEMBELAJARAN BACA TULIS QUR’AN DALAM PENINGKATAN KARAKTER SISWA SEKOLAH FULL DAY DI SMPN 1 NGIMBANG LAMONGAN - Salman Zahidi; Ahmad Zhaini (Akademika, 2018)
Efforts to improve the quality of education is constantly done, Through the program SMPN 1 Ngimbang, SMPN 1 Ngimbang program is a follow-up of Permendikhud No. 23 of 2014 concerning School Day 8 hours a day for five days, aka full day school. The learning process at SMPN 1 Ngimbangmenggunakan full day system with a good system, it can affect the success of the quality of learning that exist within the institution itself.Thesis entitled "learning effort to read writing qur'an in improving the character of school students full day smpn 1 Ngimbang" This is the result of qualitative research aimed at answering the question how to read and write qur'an in improving karaktersiswa, how important the effort to read write qur'an in increasing karaktersiswaa, apasaja supporting factors and inhibitors in reading and writing qur'an in improving the character of students in SMPN 1 Ngimbang. The research approach used was descriptive qualitative with the type of research as the case on the object. Data collection was done by interview with informant in this research that is principal, teacher, student, guardian of student.The result of the research is first, the learning effort btq that is with the learning which supported by the teacher and the student guardian. Secondly, the importance of btqa efforts in improving the character of full-time school students, such as by doing, activities - activities created by SMPN 1 Ngimbang, the facilities that support infrastructure in the implementation of the learning process. third, the supporting factor is the existence of Teacher Council, and and the professional companion teacher, and the skill in guiding the students, the liveliness and the spirit of the students in studying the science of religion, the inhibiting factors are the difference of the quality of the students in the mastery of btq science, learning in school.